Unraveling the spatial dynamics of regional economic disparities in East Java - Teguh Hadi Priyono; Edy Santoso; Nanik Istyani; Aisah Jumiati; Rafael Purtomo Somaji (Journal of Innovation in Business and Economics, 2024)
The objective of this research was to analyze the determinants of regional disparities in East Java Province. This study utilized panel data, incorporating research locations across 38 regencies in East Java, with a data series spanning from 2016 to 2020. Spatial panel data models were employed to address the research objective, specifically examining the impact of spatial and non-spatial factors on disparities in East Java. The study's findings indicated that the Spatial Autoregressive (SAR) model was the most effective for estimating disparities in the region. The effects of each variable are as follows: the average duration of schooling and investment had positive and significant effects on disparities, while the variable of open unemployment rate did not exhibit any significant effect. Additionally, there is a spatial effect in the form of an endogenous interaction effect, signifying that the extent of disparities is influenced by the disparities in neighboring areas.